(untitled) (Research, Society and Development, 2019)
The present study aimed to characterize the phytotherapic practice in primary health care units in Picos-PI. It is a quali-quantitative, descriptive and exploratory analysis. The target population of the study was defined through non-probabilistic sampling and the data were obtained based on the application of 3 distinct questionnaires directed to managers (6 participants), health professionals (25 participants), active in the Family Health Strategies and users (50 participants) of this health service in the urban area. It was observed that 92% of health professionals had good acceptance about the insertion of phytotherapy in the Unified Health Sistem. Among managers, there was unanimity regarding the implementation of herbal medicine in primary care as an alternative treatment. According to the managers interviewed, 67% of users requested alternative treatments in health facilities. However, it was observed that there are many difficulties to be faced regarding the infrastructure of services and the organization of the health system so that phytotherapy is properly applied as a support to health care, as this is a practice that can help in the maintenance. of the health conditions of the individuals. A starting point for the resolution of these questions would be to propose an academic formation and / or qualification / training about phytotherapy for health professionals and managers, because they can seek improvements in health practices, and from this users can be well oriented on the use of plants and / or herbal medicines, which will trigger several possibilities for other obstacles to be resolved and thus there are improvements in herbal practice in health services.